A STUDY OF COMMUNICATION FOR MAINTENANCE: A CASE OF SHANGHAI PORCELAIN ART INTANGIBLE CULTURAL HERITAGE - Chang, Xin; Rungsrisawat, Somdech (Veredas do Direito, 2026)
Conservation and dissemination of intangible cultural heritage (ICH) is becoming a more critical issue in the globalization and digital revolution. The case of Shanghai Porcelain Art, which is a distinct urban handicraft that combines the classical Chinese porcelain production with the aesthetics of Shanghai and a lack of interactions with the public, is explained by the limited communication possibilities and underuse of digital resources. This paper discusses the aspects of the spread of Shanghai Porcelain Art and also analyzes how digital technologies and especially virtual reality (VR) can be used to enhance the inheritance and cultural transmission of heritage. The study adopted a quantitative research design with 350 stakeholders, including inheritors, artists, cultural practitioners, students and other persons as the general population using an integrated approach with uses and Gratifications Theory, Technology Acceptance Model and immersion-based digital heritage theory. Data was analysed through descriptive statistics, correlation, regression, and mediation analyses. The results show that there exists the substantial positive correlation between digital mode of transmission and the influence of heritage of effect of Shanghai Porcelain Art (β = 0.68, p < 0.001, R2 = 0.46). The inheritance effect, in its turn, is the one that makes a strong prediction of Shanghai culture dissemination (β = 0.74, p < 0.001, R2 = 0.55). The mediation analysis proved the existence of a partially mediating effect of the relationship between digital tools and cultural dissemination, (indirect effect = 0.55, 95% CI [0.45, 0.65], p < 0.001). The theoretical contribution of the study is its relation between the immersive digital technologies and heritage learning and cultural dissemination and its practical contribution in instructing policymakers, cultural institutions, and educators in the development of VR-based platforms to transmit heritage sustainably. Digital technologies therefore contribute to deep learning as well as active cultural involvement, which will strengthen the succession and overall promotion of Shanghai Porcelain Art.